Moderation Role of Strategic Agility in the Relationship between Entrepreneurial Orientation and Competitive Advantage in SMEs - Aswan, Aswan (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This study employed dynamic ability theory to test the relationship between entrepreneurial orientation and competitive advantage moderated by strategic agility, consisting of three dimensions (strategic sensitivity, collective commitment, and fluidity of resources) in the context of small and medium enterprises in the developing country. Design/Methodology/Approach: This study applied a cross-sectional design, using bootstrapping analysis with the SmartPLS 3.0 program to test the indirect relationship between entrepreneurial orientation and competitive advantage. Strategic agility was the moderating variable to explain the relationship between entrepreneurial orientation and competitive advantage. The sample comprised 170 food and beverage small and medium enterprises (SMEs) in Sleman Regency, Yogyakarta.Research findings: The results revealed that entrepreneurial orientation increased competitive advantage through strategic agility consisting of three dimensions, simultaneously carrying out exploration and exploitation innovations to encourage entrepreneurship of SMEs in increasing sustainable competitive advantage.Theoretical contribution/Originality: The novelty of this research is the achievement of excellence and sustainable competitiveness of SMEs that can be done by increasing strategic agility.Practitioner/Policy implication: This research is expected to be the reference and consideration for SMEs' businesspeople, owners, and managers, which can be in the form of utilizing resource capabilities to encourage the improvement of company knowledge management and produce superior performance from sustainable competitors in a volatile, uncertain, and ambiguous environment.Research limitation/Implication: Future research may consider the mediating effects before the moderating variables and consider a stable environment that does not have turmoil, such as the COVID-19 pandemic, and whether strategic agility is still relevant to the research context. Further research can also prove and focus on only one scale of SMEs because they are small and medium and may have a different way of dealing with a tumultuous and uncertain environment. Finally, future researchers can also study and incorporate other entrepreneurial orientation constructs that potentially affect SMEs, such as autonomy, aggressiveness, and competitive energy.